American bison : a natural history - Lott, Dale F. (Organisms and environments, 2002)
American bison takes us on a journey into the bison's past and shares a compelling vision for its future, offering along the way a valuable introduction to North American prairie ecology. Lott explores the social life and physiology of the bison, sharing stories about its impressive physical prowess and fascinating relationships. Describing the entire grassland community in which the bison live, he writes about the wolves, pronghorn, prairie dogs, grizzly bears, and other animals and plants, detailing the interdependent relationships among these inhabitants of a lost landscape. Lott also traces the long and dramatic relationship between the bison and Native Americans, and gives a surprising look at the history of the hide hunts that delivered the coup de grace to the already dwindling bison population in a few short years. Lott also dismantles many of the myths we have created about these ways of life, and about the bison in particular, to reveal the animal itself: ruminating, reproducing, and rutting in its full glory. His portrait of the bison ultimately becomes a plea to conserve its wildness and an eloquent meditation on the importance of the wild in our lives.